2012
DOI: 10.1080/17470218.2011.626865
|View full text |Cite
|
Sign up to set email alerts
|

The Interruptive Effect of Pain on Attention

Abstract: Pain is known to disrupt attentional performance in both healthy adults and patients with chronic pain. Exactly which aspects of attentional function are affected are, however, still to be determined. The primary aim of this investigation was to systematically examine the effects of experimentally induced pain on a range of attentional performance tasks. Following a review of tests of attentional disruption, seven best candidate tasks were selected and examined across seven experiments. The tasks were: continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
189
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 189 publications
(202 citation statements)
references
References 90 publications
9
189
3
1
Order By: Relevance
“…When experiencing menstrual pain, women were generally slower or less accurate on the flanker and switching task. This is in contrast to results reported in pain induction studies, where pain seems to have specific attentional interference effects [21]. It is more difficult to directly ascertain specificity of effects for the dual (both tasks are given equal priority) and n-back tasks (no Menstrual pain and attention 20 control condition).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…When experiencing menstrual pain, women were generally slower or less accurate on the flanker and switching task. This is in contrast to results reported in pain induction studies, where pain seems to have specific attentional interference effects [21]. It is more difficult to directly ascertain specificity of effects for the dual (both tasks are given equal priority) and n-back tasks (no Menstrual pain and attention 20 control condition).…”
Section: Discussioncontrasting
confidence: 53%
“…However, for the dual task there was indirect evidence for a general pain-related effect. Here, pain produced a general decline in accuracy across both tasks, whereas in our laboratory study [21] a specific decrease in accuracy was found on the lines task, and a relative improvement on the numbers task. Overall, this would seem to suggest a general pain-related dampening effect on performance.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Curiously, while many of these studies find disrupted attention performance under pain, the specific nature of effects tends to vary, even when using identical tasks. For example, on an identical n-back task, thermal pain reduced overall accuracy 28 , while menstrual pain increased the number of false alarms 20 , and headache reduced the number of hits 30 . On a cued switching task, thermal pain increased response times (RTs) for switch but not repeat trials 28 , and menstrual and headache pain decreased accuracy overall 20 .…”
Section: Introductionmentioning
confidence: 99%